Workload and Work Stress Toward Nurses' Performance at Indonesian General Hospital - Dewi Puspaningtyas Faeni; Dela Syeikholbi; Cahyadi Husada (Dinasti Publisher, 2023)
The aim of this research is to determine the influence of workload and work stress on nurses' performance at Indonesian General Hospital. The population of the study is nurses at Indonesian General Hospital with 392 respondents as a result of Slovin formula. Respondents were based on purposive random samplings. This research is a quantitative type of research and uses distributions of questionnaires and direct data collected from all designated respondents as a methodology. Data was collected with additional focus group discussion. All data were analyzed by using SPSS, 25. With the results such as workload has a positive and significant impact on the nurses’ performance, whereas work stress and workload simultaneously have both positive impacts on the nurses’ performance.